Numerical modeling of a heat pipe transient modes - Cristiano Enke (2020)
The effect of the presence of noncondensable gas in the heat pipe was investigated experimentally and a one-dimensional numerical model was developed. The mathematical formulation includes vapor-gas compressible mixture flow conservation equations, conjugated wall, wick, and mixture energy conservation, completed with Clausius-Clapeyron saturation condition and ideal gas assumption for noncondensable gas. To solve velocity-pressure coupling a numerical iterative algorithm based on the SIMPLE method with staggered grid was used, resulting in tridiagonal matrix having an effective numerical solution. An extensive program for the model validation was performed. First, some non-trivial cases were selected from the available publications of experimental studies, like multiple heat loading and fast transients during startup and shutdown of a heat pipe with noncondensable gas. Second, some cases were performed to verify the stability of the developed algorithm under sudden changes of number and positions of heat loads and cooling zones, resulting in dynamic redistribution of mixture velocity directions and changes on noncondensable gas concentration rearrangement. Third, an experimental study was conducted in the INPE/ETE thermal laboratory following a new approach to test two identical heat pipes one with and another without noncondensable gas, under the same conditions. This new approach has allowed improving the model precision by separate adjusting of parameters that are common for both pipes. The results of simulations show that the numerical model is capable to predict the heat pipe transient performance and behavior of noncondensable gas inside the heat pipe, including a gradual formation of vapor-gas diffusion front when heat pipe approaches steady-state condition. Due to test conditions, the presented model accounts for natural and forced convection heat sink but can be easily modified to account for orbital transient heat transfer in space applications. The high dynamic transient rise and fall of temperature at startup and shutdown was in agreement with experimental results for case with and without noncondensable gas. Moreover, the temperature change rate of the condenser proved to be more sensible to the presence of noncondensable gas than temperature itself, becoming an efficient method to detect the presence of gas inside the heat pipes when the gas presence is not desirable.